Invasive rainbow trout Oncorhynchus mykiss preying on the endangered naked characin Gymnocharacinus bergii at its thermal limits. Issue 6 (27th October 2017) - Quiroga, S.; Kacoliris, F.; García, I.; Povedano, H.; Velasco, M.; Zalba, S.
Abstract : The expansion of the invasive rainbow trout Oncorhynchus mykiss into the thermal headwaters of Valcheta Stream (Patagonia, Argentina) and new predation records on the endangered endemic naked characin Gymnocharacinus bergii are presented here. These findings are discussed in relation to the contemporary evolution and thermal refuges hypothesis. This study has immediate implications for the conservation of G. bergii .